Preparation Adsorbent Chitosan of Shell Horseshoe Crab (Tachypleus gigas) and Gelatine to Reduce Pb Content - Pada Mulia Raja; Nurfajriani Nurfajriani (Jurnal Pendidikan Kimia (JPKim), 2017)
Abstract: The Porpuse of this research are to determine the preparation of chitosan from crab shell (Tachypleus gigas) and gelatine adsorbent  to reduce of Pb. This research consists of several stages: Preparation of chitosan adsorbent and crab shell (Tachypleusgigas) and gelatine and characterization of Pb after adsorbent  applied. Treatment of chitosan solution and gelatin solution with a ratio K25: G75, K50: G50 and K75: G25, then the second treatment 2% chitosan solution add gelatin powder with a variation of 0.1 g, 0.2 g, 0.3 g, 0, 4 g and 0.5 g. the results obtained by reduction of Pb optimum levels found in adsorbent of chitosan and gelatin mixture of 75%: 25% is 83.696% and 2% chitosan adsorbent mixture with the addition of 0.5 g gelatin powder that is equal to 69.316%.Keywords: adsorben, chitosan, gelatin, Pb